Desarrollo de un entorno virtual 3D para el control de presión de un sistema de aire comprimido. - Chipuxi Caiza, Christian Paúl (2021)
This project describes the application and development of a virtual pressure control environment generated in Unity dedicated to the training of skills for the recognition of parameters necessary for the selection and application of different tuning methods according to the result to be obtained in the controlled variable, We start from the transfer function of a pressure control module that is obtained analytically where it is considered the losses of the system itself and other parameters that influence the operation of the virtual plant of compressed air pressure, so that the virtual environment generated has similarity to the real world was implemented the manipulation of a manual valve in real time thus achieving generate disturbance values. The project is then divided into three phases. In the first phase there is a general description of the bibliographic concepts of industrial control processes, tuning methods, software used to generate a virtual environment, the impact it has on academic training or other areas of interest. The second phase details the process by which the similar behavior of the plant located in Arduino and the transfer function in Simulink is validated through the comparison of the responses to a unit step stimulus in open loop with the help of Matlab where the mathematical model of the Arduino programming was entered. In the last phase the measurements of the time in which the system reaches stability with the help of the PLC controller S7-1200 are made to verify that the tuning values found analytically respond favorably.